A prospective examination of asthma symptom monitoring: provider, caregiver and pediatric patient influences on peak flow meter use. (February 2014) - Ayala, Guadalupe X.; Gillette, Chris; Williams, Dennis; Davis, Stephanie; Yeatts, Karin B.; Carpenter, Delesha M.; Sleath, Betsy
Abstract Objective: This study examined whether provider, caregiver and child communication predicted peak flow meter (PFM) use one month later. Methods: Five practices, 35 providers and 296 children with persistent asthma and their caregivers comprised the study sample. Audio-recorded provider–caregiver–child communication during the baseline medical visit captured discussion of the PFM; and child and caregiver baseline interviews after the medical visit collected factors associated with PFM use. Child- and caregiver-reported PFM availability and use, and observed child use of PFM were collected one-month later in the family's home. Results: During the medical visit, provider communication about PFM use was infrequent (10% maximum) and child- or caregiver-initiated communication was nearly absent (0%–2%). Despite this, children demonstrated good use of the PFM one month later. Children were significantly more likely to perform at least six PFM steps correctly one month later when there was more communication about PFM during the medical visit. Few other factors predicted availability and use. Conclusions: Few providers discussed use of a PFM; observed performance was predicted by having talked about it with the child's provider. Provider communication should be targeted in future interventions to improve asthma management skills.